Mapping Indigenous Knowledge in the Digital Age - Thumbadoo, Romola V.; Taylor, D. R. Fraser (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, "Mapping Indigenous Knowledge in the Digital Age", explores Indigenous engagement with geo-information in contemporary cartography. Indigenous mapping, incorporating performance, process, product, and positionality as well as tangible and intangible heritage, is speedily entering the domain of cartography, and digital technology is facilitating the engagement of communities in mapping their own locational stories, histories, cultural heritage, environmental, and political priorities. In this publication, multimodal and multisensory online maps combine the latest multimedia and telecommunications technology to examine data and support qualitative and quantitative research, as well as to present and store a wide range of temporal/spatial information and archival materials in innovative interactive storytelling formats. It will be of particular interest to researchers engaged in studies of global human and environmental connection in the age of evolving information technology.